Individual Differences Among Children in Sucrose Detection Thresholds: Relationship With Age, Gender, and Bitter Taste Genotype. Issue 1 (January 2016) - Joseph, Paule Valery; Reed, Danielle R.; Mennella, Julie A.
Abstract : Background: Little research has focused on whether there are individual differences among children in their sensitivity to sweet taste and, if so, the biological correlates of such differences. Objectives: Our goal was to understand how variations in children's sucrose detection thresholds relate to their age and gender, taste genotype, body composition, and dietary intake of added sugars. Methods: Sucrose detection thresholds in 7- to 14-year-old children were tested individually using a validated, two-alternative, forced-choice, paired-comparison tracking method. Five genetic variants of taste genes were assayed: TAS1R3 and GNAT3 (sweet genes; one variant each) and the bitter receptor gene TAS2R38 (three variants). All children were measured for body weight and height. A subset of these children were measured for the percentage of body fat and waist circumference and provided added sugar intake by 24-hour dietary recall. Results: Sucrose thresholds ranged from 0.23 to 153.8 mM with most of the children completing the threshold task (216/235; 92%). Some children were biologically related (i.e., siblings), and for the genetic analysis, one sibling from each family was studied. Variants in the bitter but not the sweet genes were related to sucrose threshold and sugar intake; children with two bitter-sensitive alleles could detect sucrose at lower concentrations ( F (2, 165) = 4.55, p = .01; rs1726866) and reported eating more added sugar (% kcal; F (2, 62) = 3.64, p = .03) than did children with less sensitive alleles. Age, gender, and indices of obesity also were related to child-to-child differences in sucrose threshold; girls were more sensitive than boys ( t (214) = 2.0, p = .05), older children were more sensitive than younger children ( r (214) = −.16, p = .02), and fatter ( r (84) = −.22, p = .05) or more centrally obese children ( r (84) = −.26, p = .02) were more sensitive relative to others. Discussion: Inborn differences in bitter sensitivity may affect childhood dietary sugar intake with long-term health consequences. There may be a more complex interplay between the developing bitter and sweet taste systems than previously understood.